Optimization Of A 20 Kv Capacitor Bank Energy Management System For Electrical Usage In Indihome Network Devices - Mendrofa, Dicky Efelin Teoly; Dalimunthe, Muhammad Erpandi; Erivianto, Dino (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
The increasing demand for stable and efficient electrical energy in telecommunication systems, particularly in IndiHome network infrastructure, requires a reliable energy management strategy. One of the key challenges faced is the presence of reactive power, which can reduce power factor efficiency and lead to higher energy losses. This study focuses on optimizing the energy management system using a 20 kV capacitor bank to improve power factor and reduce electrical losses in IndiHome network devices. The research involves the design, implementation, and analysis of a capacitor bank control system that responds dynamically to load variations. Through simulation and real-time testing, the system is evaluated based on its ability to maintain a high power factor, reduce energy consumption, and stabilize voltage levels. The results show that the optimized capacitor bank system can improve power factor to above 0.95 and reduce reactive power demand significantly, resulting in improved overall energy efficiency. This optimization not only reduces operational costs but also enhances the reliability and longevity of network equipment by minimizing voltage drops and harmonic disturbances. The study concludes that capacitor bank-based energy management systems are highly effective and essential for modern telecommunication infrastructure. Keyword : Capacitor Bank, Power Factor, Energy Management, Telecommunication, IndiHome, 20 kV, and Reactive Power